RADIATION SHIELDING STUDY FOR THE VERTICAL TEST SYSTEM FOR SUPERCONDUCTING RF CAVITIES. Issue 1 (19th December 2018) - Zhou, Dejun; Lin, Lin; Feng, Liwen; Quan, Shengwen
Abstract: A vertical test system (VTS) for superconducting radio frequency cavities had been designed and constructed at Peking University. During the test, field emission electrons in the cavity will be accelerated and some of them will hit the flange of cavity with high-energy. These high-energy electrons will have a significant impact on the radiation safety of the system and environment. In this paper, the Particle-in-Cell solver in CST software was used to analyze the behavior of electrons emitted from different field emission positions and found the worst field emission site which deposited the most energy on the cavity wall. The impact information of the electrons emitted from the worst field emission site was utilized to character the source term. Prompt dose equivalent rate distribution and residual radioactivity was predicted by using the Monte Carlo simulation program FLUKA. Further vertical test results are consistent with the simulation results.